Endoscopic Endonasal versus Transcranial Optic Canal Decompression: A Morphometric, Cadaveric Study - Kim, Jun; Plitt, Aaron R; Vance, Awais; Connors, Scott; Caruso, James; Welch, Babu; Garzon-Muvdi, Tomas (Journal of Neurological Surgery Part B: Skull Base, 2021)
Introduction Decompression of the optic nerve within the optic canal is indicated for compressive visual decline. The two most common approaches utilized for optic canal decompression are a medial approach with an endoscopic endonasal approach and a lateral approach with a craniotomy. Our study is a cadaveric anatomical study comparing the length and circumference of the orbit decompressed via an endoscopic endonasal approach versus a frontotemporal craniotomy.Methods Five cadaveric specimens were utilized. Predissection computed tomography (CT) scans were performed on each specimen. On each specimen, a standard frontotemporal craniotomy with anterior clinoidectomy and superolateral orbital decompression was performed on one side and an endoscopic endonasal approach with medial wall decompression was performed on the contralateral side. Post-dissection CT scans were performed. An independent radiologist provided measurements of the length (mm) and circumference (degrees) of optic canal decompression bilaterally.Results The mean length of optic canal decompression for open and endoscopic approach was 13 mm (range 12–15 mm) and 12.4 mm (range 10–16 mm), respectively. The mean circumference of decompression for open and endoscopic approaches was 252.8 degrees (range 205–280 degrees) and 124.6 degrees (range 100–163 degrees), respectively.Conclusion The endoscopic endonasal and the transcranial approaches provide a similar length of optic canal decompression, but the transcranial approach leads to greater circumferential decompression. The endoscopic endonasal approach has the benefit of being minimally invasive, though. Ultimately, the surgical approach decision should be based on the location of the pathology and the surgeon's comfort.
Keywords: orbit; optic canal; optic canal decompression; endoscopic endonasal approach; frontotemporal craniotomy